Perbedaan Persepsi Mahasiswa Akuntansi Mengenai Faktor-Faktor yang Mempengaruhi Pemilihan Karir - Nirmala, Adinda Putri; Elvira, Icha (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to analyze the factors influencing career choices among accounting students. Various factors investigated include financial compensation, professional training, professional recognition, social values, work environment, labor market aspects, personality, and more. A quantitative approach was used to collect data through a survey of accounting students at Universitas Nasional Surabaya. The analysis found that students' perceptions of these factors vary depending on the type of career they choose, such as auditor, corporate accountant, or government accountant. Financial rewards and professional training stood out as significant influencing factors, while the influence of social values and work environment was less significant. This study will make an important contribution to educational institutions in developing appropriate curricula and help companies understand the preferences of future accountants to create a more supportive work environment. The results can also serve as a reference for developing accounting careers that better align with labor market needs..